Lethal and sub-lethal effects of copper to the African catfish (Clarias gariepinus) juveniles (2004)
Lethal and sub-lethal effects of copper on Clarias gariepinus were studied using a 96-hour static bioassay. Copper (as copper chloride, CuCl2 . H2O) was used to prepare the stock solution from which five standard concentrations 0.0, 1.8, 3.2, 5.6, and 10.0 mg/L were prepared (coded A – E). 15 juvenile C. gariepinus fish having a mean weight and length 5.8g and 18 cm respectively were used. The 96-hour LC50 estimated using the logarithm method were 0.6, 0.71 and 0.7 mg/l for replicates 1, 2 and 3 respectively with mean as 0.67mg/l. Haematological changes were generally not significant (P> 0.05). Copper concentrations in bone and muscle-tissues were also determined. The mean copper concentration in bone ranged from 1.86 (treatment A) to 17.04 ppm (Treatment E) and muscle 1.29 (treatment A) to 55.5 ppm (treatment E). There were significant differences (p<0.05) in mortality among treatments